2021
DOI: 10.1121/10.0004770
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual analysis of directional late reverberation

Abstract: The late reverberation characteristics of a sound field are often assumed to be perceptually isotropic, meaning that the decay of energy is perceived as equivalent in every direction. In this paper, we employ Ambisonics reproduction methods to reassess how a decaying sound field is analyzed and characterized and our capacity to hear directional characteristics within late reverberation. We propose the use of objective measures to assess the anisotropy characteristics of a decaying sound field. The energy-decay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…In rooms, diffuse reverberation typically dominates the after the third reflection order (Kuttruff, 1995). Depending on room geometry and the spatial distribution of sound absorption at room boundaries, the resulting late reverberation can be considered approximately spherically isotropic (Hodgson, 1996) or anisotropic when containing limited spatial directivity (Alary et al, 2019a; Lachenmayr et al, 2016; Luizard et al, 2015; Romblom et al, 2016). For simplicity, cases with a spatially highly uniform incidence of late reverberation are assumed to approximate properties of a diffuse sound field and are referred to as isotropic here, although the reverberant sound field does not become isotropic in a strict sense (Polack, 1993; Jeong, 2016; Nolan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In rooms, diffuse reverberation typically dominates the after the third reflection order (Kuttruff, 1995). Depending on room geometry and the spatial distribution of sound absorption at room boundaries, the resulting late reverberation can be considered approximately spherically isotropic (Hodgson, 1996) or anisotropic when containing limited spatial directivity (Alary et al, 2019a; Lachenmayr et al, 2016; Luizard et al, 2015; Romblom et al, 2016). For simplicity, cases with a spatially highly uniform incidence of late reverberation are assumed to approximate properties of a diffuse sound field and are referred to as isotropic here, although the reverberant sound field does not become isotropic in a strict sense (Polack, 1993; Jeong, 2016; Nolan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Is the highest degree of envelopment elicited by a stationary and isotropically diffuse sound field, or by a sound field that exhibits audible spatio-temporal fluctuations / modulations? These questions are relevant in the technical design and creative application of artificial reverberators [19,20,21,22,23], spatial sound synthesis techniques [3,24,25], and spatial upmixing algorithms [26,27].…”
Section: This Motivates the Following Research Questionsmentioning
confidence: 99%
“…In a coherence-based estimation of the mixing time, the moving short-time interaural cross-correlation STIACC can be helpful. However, Alary et al (2021) analyzed spatial room impulse responses (SIR) recorded with a 32-channel spherical microphone array. They determined a mixing time defined by a stable minimum of coherence and showed that after this mixing time, still directional components can be found in the reverberation of the considered concert halls.…”
Section: Required Accuracy Of Physical Propertiesmentioning
confidence: 99%